2018
DOI: 10.21037/jtd.2018.01.157
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery and video-assisted thoracic surgery lobectomy: the Italian VATS Group* surgical protocol

Abstract: Enhanced recovery after surgery (ERAS) is a strategy that seeks to reduce patients' perioperative stress response, thereby reducing potential complications, decreasing hospital length of stay and enabling patients to return more quickly to their baseline functional status. The concept was introduced in the late 1990s and was first adopted in patients undergoing open colorectal surgery. Since then, the concept of ERAS has been adopted by multiple surgical specialties. The diffusion of video-assisted thoracic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
(48 reference statements)
0
27
0
3
Order By: Relevance
“…From its introduction at the start of 1990s, ERAS has improved perioperative approach of many specialities: general surgery (colon resection) [4], vascular surgery [5], thoracic surgery [6,7] and recently urology (cystectomy) [8,9]. The aim of such programmes is to try to change the physiological and psychological responses to major surgery [1]: the experiences collected until now have shown a reduction in complications and hospital stay, improvements in cardiopulmonary function, earlier return of bowel function and earlier resumption of normal activities [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…From its introduction at the start of 1990s, ERAS has improved perioperative approach of many specialities: general surgery (colon resection) [4], vascular surgery [5], thoracic surgery [6,7] and recently urology (cystectomy) [8,9]. The aim of such programmes is to try to change the physiological and psychological responses to major surgery [1]: the experiences collected until now have shown a reduction in complications and hospital stay, improvements in cardiopulmonary function, earlier return of bowel function and earlier resumption of normal activities [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Additional challenges unique to thoracic surgery include the physiologic insult caused by one lung ventilation intraoperatively and pain from intercostal incisions limiting respiratory effort. There are currently no consensus guidelines from the ERAS group for general thoracic surgery; however, several groups have published their initial experiences with enhanced recovery protocols (3)(4)(5)(6)(7)(8)(9)(10). Common elements include preoperative optimization with smoking cessation and preoperative exercise regimens, intraoperative care modifications with a focus on minimally invasive techniques, drain limitation, and long term narcotic avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…However, when challenged in the literature, four randomized controlled trials (RCTs) (2-5), one non-RCT (6), and two meta-analyses (7,8) found no benefit to leaving a second chest tube in place. As a result, most ERAS protocols leave only one chest tube following a pulmonary resection (9).…”
mentioning
confidence: 99%
“…Explanations for the inconsistent findings have been previously proposed (11): (I) if the true benefit with or without applied external suction is small, inconsistencies between studies may not detect a true difference; (II) assessments of air leaks has been shown to be inconsistent even with experienced clinical teams (19); (III) lastly, there may be no physiologic benefit or risk to applied external suction after pulmonary resection. Acknowledging the controversies, two programs aimed at standardizing air leak management after pulmonary resection have set a regimen of setting chest drains to applied external suction until postoperative day (POD) 1, then moving to no applied external suction unless there is an adverse event (9,12). With consistent protocolized care offered by ERAS programs and more objective assessment of air leaks offered by digital drains, large multi-center RCT may help establish the best regimen for the use of applied external suction in the postoperative period.…”
mentioning
confidence: 99%
See 1 more Smart Citation